2017
DOI: 10.3233/cbm-170167
|View full text |Cite
|
Sign up to set email alerts
|

Propofol-induced neurotoxicity in hESCs involved in activation of miR-206/PUMA signal pathway

Abstract: Propofol induce s cell death in hESC-derived neurons via activation of miR-206/PUMA signal pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 31 publications
0
15
1
Order By: Relevance
“…In fact, several previous studies have implicated the functions of propofol on miRNA expression. For example, miR‐372, miR‐195, miR‐1284, miR‐206, miR‐9 and miR‐21 were all stated to be affected by propofol to control cell growth, migration and invasion . Additionally, here ADAM8 was identified to directly target to miR‐328.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, several previous studies have implicated the functions of propofol on miRNA expression. For example, miR‐372, miR‐195, miR‐1284, miR‐206, miR‐9 and miR‐21 were all stated to be affected by propofol to control cell growth, migration and invasion . Additionally, here ADAM8 was identified to directly target to miR‐328.…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-372, miR-195, miR-1284, miR-206, miR-9 and miR-21 were all stated to be affected by propofol to control cell growth, migration and invasion. [14][15][16][17][18][19] Additionally, here ADAM8 was identified to directly target to miR-328. Our results implicate that propofol exerts an inhibitory effect on pancreatic cancer cell growth, migration and invasion by enhancing miR-328 which targets ADAM8.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] Further, miR-206 knockdown was shown to protect human embryonic stem cells (hESCs) against propofol-induced cell apoptosis, thereby inhibiting neurotoxicity. 20 Rho-associated coiled coil-containing protein kinase 1 (ROCK1) is a protein serine/threonine kinase and a major regulator of the actomyosin cytoskeleton, thereby governing various cellular processes, including cell division, adhesion, contraction, migration, apoptosis, and proliferation. 21 Accumulating studies have indicated that ROCK1 plays crucial roles in cancer development by modulating diverse vital cellular biological processes related to malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…Total RNA was isolated from hESC-derived neurons with TRIzol reagent (Invitrogen, Shanghai, China) and reverse-transcribed into cDNA using oligo (dT) 15 and ReverTra Ace reverse transcriptase (Toyobo, Osaka, Japan). NanoDrop 2000 (Thermo Scientific, Wilmington, DE, USA) was used to quantify amounts of mRNA.…”
Section: Rna Extraction and Real-time Qrt-pcrmentioning
confidence: 99%
“…Li et al have reported that propofol induces cell apoptosis in hESC-derived neurons via activation of the miR-206/PUMA signal pathway [14]. And Jiang et al have reported that propofol inhibits hESCs neurogenesis through a mechanism involving the miR-141-3p/IGF2BP2 axis [15].…”
Section: Introductionmentioning
confidence: 99%